Influence of the insecticide λ-cyhalothrin on oxidative stress and expression of replicative protein A in the brain of fish - V. S. Nedzvetsky; V. Y. Gasso; R. O. Novitskiy; S. V. Yermolenko (Agrology, 2020)
Anthropogenic pollution of natural waters by pesticides became a global problem with the beginning of their widespread use in the 1960s of the twentieth century. The most studied cells’ response to the pesticides is an increase in the content of reactive oxygen species (ROS) and, as a consequence, the development of oxidative stress. The proliferative activity of cells is regulated by various factors and largely depends on the expression of proteins involved in the DNA replication. Among such proteins are replicative proteins A (RPA), which binds single-stranded DNA (ssDNA) of eukaryotes. Disruption of RPA-associated cellular activity initiates genomic imbalance, so the expression and content of RPA1 serves as a marker not only of the cell cycle stability, but also the relevant response to DNA damage caused by ecotoxicants.The aim of our study is to determine the oxidative stress development and the RPA1 protein state as a response of rainbow trout’s brain cells to the influence of sublethal concentrations of the lambda-cyhalothrin. A model experiment on the neurotoxicity of lambda-cyhalothrin was performed on the rainbow trout (Oncorhynchus mykiss) under experimental conditions in a la-boratory. The obtained results indicate that sublethal concentrations of lambda-cyhalothrin in the water induce a significant increase in ROS generation in the rainbow trout’s brain. It was found that the content of ROS in the fish brain in all experimental groups depends on both the lambda-cyhalothrin concentration and the duration of exposure to the pesticide. Oxidative stress under the influence of lambda-cyhalothrin increases the content of stress-regulating protein RPA1 in the fish brain, inhibits transcriptional activity and limits the DNA breaks repair, which, in turn, can lead to genomic instability and activation of apoptosis. This indicates a high sensitivity of the mechanism of DNA replication to the neurotoxic effect of synthetic pyrethroids. Thus, the detected increased expression of RPA1 protein may be an adequate biomarker of cellular response to the toxic effects of synthetic pyrethroids in the brain of fish. Further studies of the effect of pyrethroids on key proteins of the aquatic organisms’ reaction to intoxication are of great importance for the determination of indicative biomarkers of pesticide pollution and its potential risk